Technical change and the elasticity of factor substitution - Jürgen Antony (Hochschule Pforzheim, 2014)
This paper addresses the relationship between technical change and the elasticity of substitution between factors of production. It is shown how the elasticity within a CES production setting can change due to technical change. Technical change is interpreted in the spirit of horizontal differentiation as in many growth models. Cases for positive and negative returns to differentiation are analyzed which can be understood as progress or complexity congestions. It is shown how the elasticity changes due to technical choices for each of them.
urn:nbn:de:bsz:951-opus-374
Keywords: E23; O33; F41; J24; 330; Elasticity of substitution; CES production function; Inequality